Advancing Universal Health Coverage : What Developing Countries Can Learn from the English Experience? - Smith, Peter C. (World Bank, Washington, DC, 2018)
The United Kingdom has in many respects the archetypal centrally planned, publicly financed health care system in the form of National Health Service (NHS), established in 1948 in a time of great austerity after Second World War. It is largely funded from general taxation, and provides wide coverage of most mainstream health services, with little recourse to user charges. It offers strong financial protection against the costs of health care and enjoys high public approval ratings. Its principal shortcomings have been weaknesses in service quality, often in the form of long waiting times, and sometimes relating to clinical quality. This paper concentrates on the experience in England, which accounts for 84 percent of the UK population of 64.6 million. The system of health service coverage adopted in the NHS is very simple. There is no explicit requirement to enroll in an insurance plan. Instead, citizens must register with a general practitioner (GP) of their choice. GPs act as a gatekeeper to nonemergency secondary care and prescription medicines and devices. Apart from small fees for some prescription medicines (from which many citizens are exempt), patients are not directly charged for access to NHS care. Throughout most of its history, the NHS model of governance has entailed strong central control by the national ministry, with local administration responsible for detailed local planning and purchasing. The forms of local administration have varied. In the early years of the NHS they were primarily local NHS hospitals, with separate committees for oversight of primary care. Since 1974, local health authorities have assumed the role of oversight of local services, currently covering, on average, populations of 250,000.